Effects of treatment with chemotherapy and/or tamoxifen on the biomarkers of cardiac injury and oxidative stress in women with breast cancer. Issue 47 (November 2017) - Silva, Fabricio Bragança; Romero, Walckiria Garcia; Carvalho, Ana Ligia Rodrigues de Abreu; Souza, Gleyce Ariadne Alves; Claudio, Erick Roberto Gonçalves; Abreu, Glaucia Rodrigues
Abstract : Abstract: There has been an increase in deaths from cardiovascular diseases following breast cancer therapy. Evidence has shown that this outcome is, in part, associated with cardiotoxicity induced by the chemotherapeutic drugs and the increase in oxidative stress. The aim of this study was to evaluate the effects of chemotherapy and hormone therapy with tamoxifen on the biomarkers of cardiac injury and oxidative stress in women with breast cancer. Thirty women were followed-up for 1 year and were divided into 3 groups according to the treatment protocol: women treated only with tamoxifen and clinical follow up for 12 months (Tam, n = 10); women treated only with chemotherapy for 6 months with clinical follow up for an additional 6-month period (Chemo, n = 10); and women who received chemotherapy for 6 months followed by a 6-month period only with tamoxifen therapy and clinical follow up (Chemo + Tam, n = 10). Analysis of the blood levels of cardiac troponin I (cTnI), advanced oxidation protein products (AOPP) and the activity of the plasmatic isoform of the antioxidant enzyme glutathione peroxidase (GPx) was performed before treatment (T0) and at 6 (T6) and 12 (T12) months after treatment. The Chemo group showed higher levels of cTnI (0.065 ± 0.006 ng/mL, P  < .05) and AOPP (4.99 ± 0.84 μmol/L, P  < .05) and reduced GPx activity (24.4 ± 1.1 nM/min/mL, P  < .05) at T12 than the Tam group (cTnI: 0.031 ± 0.001 ng/mL; AOPP: 1.40 ± 0.10 μmol/L; GPx: 28.0 ± 0.7 nM/min/mL) and Chemo + Tam group (cTnI: 0.037 ± 0.002 ng/mL; AOPP: 2.53 ± 0.30 μmol/L; GPx: 29.5 ± 1.0 nM/min/mL). These data support the hypothesis that long-term oxidative stress after chemotherapy may have an impact on cardiovascular diseases and that tamoxifen has cardioprotective effects.